AUTOIMMUNE LIVER DAMAGE IN PATIENT WITH LYELL`S SYNDROME - Талицкая, Елена Анатольевна; Близнюк, Алексей Анатольевич; Саблина, Ольга Константиновна; Калитина, Светлана Владимировна (Medicine in Kuzbass, 2019)
Autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), primary sclerosing cholangitis (PSC) are independent liver diseases. But in some cases, patients have syndromes of several liver disease. Overlap-Syndrome sclerosing cholangitis / autoimmune hepatitis by definition from EASL recommendation is ill-defined immune disorders with characteristic histological features of autoimmune hepatitis and typical cholangiographic signs of sclerosing cholangitis. Patients with overlap-syndrome sclerosing cholangitis / autoimmune hepatitis in 1,4-17 % cases.Goal – the main goal is to describe rare clinical case combined autoimmune damage to the liver, skin and mucous membranes.Results. In the article rare clinical case of autoimmune liver damage is described in the way of overlap-syndrome sclerosing cholangitis / autoimmune hepatitis, simultaneously with autoimmune disease of the skin and mucous membranes in the form of severe toxic-allergic epidermal necrolysis, Lyell`s syndrome. Also the process of clinical symptoms and their reverse evolution is shown.Application. Gastroenterology.
Keywords: autoimmune hepatitis; primary sclerosing cholangitis; primary biliary cirrhosis; Lyell’s syndrome